Actitud y conocimiento sobre la donación de órganos en los estudiantes de la Carrera de Medicina del Área de la Salud Humana Loja - Ecuador - Camacho Troya, Michelle Ariana (2016)
Organ donation is linked to the manifestation of a person's willingness to permit the use of all or part of his/her body in life or after death. That is the reason for this study, called: THE ATTITUDE AND KNOWLEDGE OF MEDICAL STUDENTS FROM THE FACULTY OF HUMAN HEALTH IN LOJA ECUADOR REGARDING ORGAN DONATION. The investigation's objectives were: to determine the attitude toward organ donation among students of the human health faculty; to assess the degree of knowledge that students of the human health faculty possess in regards to organ donation; and to develop a proposal for information for the study population about organ donation and its benefits in order to raise awareness within the students and through them within the community about the importance of donating. This study was qualitative-descriptive-cross sectional in nature, all students studying medicine in the faculty of human health were selected, comprising a sample of 86 students. Ninety-two percent have a good attitude regarding organ donation, 64% think it is a way of giving life, 10% would donate for solidarity and 8% of respondents are against donating for various reasons. Ninety-nine percent understand that there are diseases in which a transplantation is the definitive treatment to save a life and finally 97% were willing to receive an organ if their life depended on it. Keywords: Attitude, knowledge, organ donation and students